Genetic regulation of liver lipids in a mouse model of insulin resistance and hepatic steatosis. Issue 1 (8th January 2021) - Norheim, Frode; Chella Krishnan, Karthickeyan; Bjellaas, Thomas; Vergnes, Laurent; Pan, Calvin; Parks, Brian W; Meng, Yonghong; Lang, Jennifer; Ward, James A; Reue, Karen; Mehrabian, Margarete; Gundersen, Thomas E; et al.
Abstract: To elucidate the contributions of specific lipid species to metabolic traits, we integrated global hepatic lipid data with other omics measures and genetic data from a cohort of about 100 diverse inbred strains of mice fed a high‐fat/high‐sucrose diet for 8 weeks. Association mapping, correlation, structure analyses, and network modeling revealed pathways and genes underlying these interactions. In particular, our studies lead to the identification of Ifi203 and Map2k6 as regulators of hepatic phosphatidylcholine homeostasis and triacylglycerol accumulation, respectively. Our analyses highlight mechanisms for how genetic variation in hepatic lipidome can be linked to physiological and molecular phenotypes, such as microbiota composition. Synopsis: A survey of hepatic lipidome in a cohort of genetically diverse mice on high‐fat/high‐sucrose diet identifies novel modulators of liver lipid metabolism in the context of hepatic steatosis. The association between lipids, gene expression and metabolic traits is mapped. Network modeling identifies co‐regulated modules of hepatic lipids. Association mapping prioritizes potential drivers of hepatic lipid metabolism. Identification and validation of Ifi203 and Map2k6 as regulators of specific hepatic lipids. Abstract : A survey of hepatic lipidome in a cohort of genetically diverse mice on high‐fat/high‐sucrose diet identifies novel modulators of liver lipid metabolism in the context of hepatic steatosis.